Chronic exposure to arsenic and high fat diet additively induced cardiotoxicity in male mice - Akram Ahangarpour; Leila Zeidooni; Azin Samimi; Soheila Alboghobeish; Laya Sadat Khorsandi; Mitra Moradi (Wolters Kluwer Medknow Publications, 2018)
Diet is one of the important risk factors that could potentially affect arsenic-induced cardiotoxicity. The present study was undertaken to investigate the effect of high fat diet on arsenic-induced cardiotoxicity in mice. Mice were divided into six different groups (n = 12), two control groups received either low fat diet (LFD) or high fat diet (HFD) along with deionized drinking water and four test groups given LFD + 25 ppm arsenic, LFD + 50 ppm arsenic, HFD + 25 ppm arsenic, and HFD + 50 ppm arsenic in drinking water for 5 months. The body weight, heart weight to body weight ratio, cardiac biochemical markers, lipid profile, and histological examination of heart were evaluated. The results demonstrated that arsenic exposure led to a significant decrease in heart glutathione level, catalase enzyme activity, and a significant increase in reactive oxygen species (ROS), malondialdehyde levels, and biochemical enzymes. The administration of HFD resulted in above-mentioned changes as well as an alteration in lipid profile; however, arsenic exposure alone or along with HFD caused a reduction in lipid profile factors, except HDL level. Our results revealed that HFD increased arsenic-induced heart injury in the mice. This effect may be because of reduction in antioxidant activities and/or increase in oxidative stress and ROS in mice heart tissues. These findings could be important for clinical intervention to protect against or prevent arsenic-induced cardiotoxicity in humans.